Sustainable Banking and Bank Performance - Handajani, Lilik; Akram, Akram; Rifai, Ahmad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021)DO - 10.24843/JIAB.2021.v16.i01.p12, 2021)
This research aims to examine the impact of sustainable banking practices and bank characteristics on bank performance. Structural equation models were used to analyze 11 banks listed on the Indonesia Stock Exchange that published sustainability reports consistently during the periods of 2015–2018. Results indicate that while the internalization of sustainability issues in banking business practices does not have a significant impact on bank performance, the characteristics of a bank, which are reflected by institutional and foreign ownership and bank age, have a significant effect on bank financial and nonfinancial performance. The implications of sustainable banking practices are indicated to gain legitimacy from regulators for the existence of financial entities and meet stakeholder expectations, which in practice require trade-off of interests among stakeholder groups. Keywords :  sustainable banking, bank performance,  bank characteristic